Mapeamento e caracterização de acidentes envolvendo tratores nas rodovias federais brasileiras que cortam o Estado de Minas Gerais - Lopes, José Evanaldo Lima (2015)
One of the main factors responsible for the increasing development of the Brazilian agricultural sector was the inclusion of agricultural mechanization in agriculture, where the tractor was the key element, however, with the increase in the number of tractors, now occur many accidents involving these machines during displacement on the roads and in carrying out operations in the fields. While it is common accidents involving tractors and nonagricultural in the Brazilian federal highways, there is a survey of the geographical distribution of the occurrence points and the characterization of these accidents in the country and especially in the state of Minas Gerais, which presents some characteristics from one extensive road network and a strategic location with important roads linking major economic centers of the country. The objective of this paper perform the mapping and characterization of accidents involving tractors in federias highways crossing the state of Minas Gerais. This research was conducted in the Accident Research Laboratory with Agricultural Machinery (LIMA), belonging to the Federal University of Ceará (UFC), with 148 accidents involving data collected tractors from January 2008 to September 2011 and obtained through a partnership between the LIMA and the 16th Superintendence of the Federal Highway Police -PRF state of Ceará. For the mapping of points of accidents was used ArGIS 9.3® software, the characterization was performed by descriptive statistics of frequency analysis and to analyze the spatial dependence of the evaluated attributes was used Gs + ® software. From the results it was concluded that use of GIS tools proved to be effective in the mapping of accidents with tractors in federias highways in the state of Minas Gerais, the Metropolitan mesoregion of Belo Horizonte highest number of accidents with 53 occurrences, tractors wheels were responsible for 129 accidents, the federal highway with highest record of accidents was BR 381 with 40 accidents, in the afternoon there were 62 accidents, collisions accounted for 114 accidents. The age group most operators involved in accidents was between 20 to 29 years, the cause of most accidents observed was the lack of attention, with 54 cases and 93 accidents occurred weather conditions from clear skies and good visibility. Kriging technique was efficient in the study of accidents with tractors in the state of Minas Gerais.